2011
DOI: 10.1260/0144-5987.29.6.797
|View full text |Cite
|
Sign up to set email alerts
|

Research on Heavy Oil Thermal Recovery by CO2 Steam Flooding with Help of Combination of Borehole-Surface Electric Potential and Cross-Borehole Electric Potential

Abstract: With an increasing tendency towards more demand for energy resources, the supply of energy as a focus of global strategy is attracting more and more attention from the world. However, on the one hand, conventional hydrocarbon resources are decreasing gradually, and therefore it is definitely an urgent task to search for renewable and replaceable resources at the present time. On the other hand, it has been proved that the total reserves of heavy oil are already up to 1105×108 tons around the world, which means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Experimental studies and reservoir simulations on CO 2 and hydrocarbon mixtures were carried out to improve hydrocarbon recovery. Pressure/volume/temperature (PVT) studies and core flood experiments indicated that the important mechanism for hydrocarbon recovery by gas injection was mainly a hydrocarbon volume increase and viscosity reduction, and pure CO 2 appeared to be the best recovery agent. Some authors have investigated the potential of carbonated (CO 2 -enriched) water injection for improving recovery from hydrocarbon reservoirs with the added benefit of safe storage of CO 2 by conducting high-pressure flow visualization, core flood experiments, and detailed compositional simulation at reservoir conditions. , In addition to time-consuming experimental methods and reservoir models, CO 2 -hydrocarbon solubility parameters have been obtained from correlations available in the literature. , Recently, the solubility and self-diffusion of carbon dioxide and hydrogen sulfide in linear polyethylene melts and brines were reported. , Attempts to understand the thermal behavior at hydrocarbon-solid surfaces have been made using molecular modeling by a number of authors. There has been extensive research on the effect of CO 2 dissolution on hydrocarbon viscosity, and many correlations have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies and reservoir simulations on CO 2 and hydrocarbon mixtures were carried out to improve hydrocarbon recovery. Pressure/volume/temperature (PVT) studies and core flood experiments indicated that the important mechanism for hydrocarbon recovery by gas injection was mainly a hydrocarbon volume increase and viscosity reduction, and pure CO 2 appeared to be the best recovery agent. Some authors have investigated the potential of carbonated (CO 2 -enriched) water injection for improving recovery from hydrocarbon reservoirs with the added benefit of safe storage of CO 2 by conducting high-pressure flow visualization, core flood experiments, and detailed compositional simulation at reservoir conditions. , In addition to time-consuming experimental methods and reservoir models, CO 2 -hydrocarbon solubility parameters have been obtained from correlations available in the literature. , Recently, the solubility and self-diffusion of carbon dioxide and hydrogen sulfide in linear polyethylene melts and brines were reported. , Attempts to understand the thermal behavior at hydrocarbon-solid surfaces have been made using molecular modeling by a number of authors. There has been extensive research on the effect of CO 2 dissolution on hydrocarbon viscosity, and many correlations have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy oil exploitation has a significant impact on the pattern of world oil production. However, heavy oil has the characteristics of high colloid and asphaltene content, high viscosity and density, and poor flow capacity, resulting in great difficulty and high production cost of recovering heavy oil [1][2][3][4]. For ordinary heavy oil reservoirs, due to adverse mobility ratio between water and oil, the fingering effect occurs and the oil recovery efficiency of conventional water flooding is low.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy oil resources as one of the most important unconventional resources are widely distributed in several countries such as China, Canada, and Venezuela. The viscosity of heavy oil typically ranges from 50 to 50000 mPa•s at reservoir temperature and pressure [1][2][3][4][5]. Water flooding is recognized as one of the most common secondary oil recovery techniques after primary production period, which has been widely applied for the recovery of light oil.…”
Section: Introductionmentioning
confidence: 99%